A comparison of strawberry cultivation: case study of selected farms in Malaysia and Japan - Shamsudin, Rosnah; Hamzah, Hanny Zurina; Shuso, Kawamura; Yasunaga, Eriko; Kamarul Zaman, Amanina Amani (Human Resource Management Academic Research Society, 2020)
Strawberries are non-climate crops that can be planted both in temperate and seasonal climate regions and are popular among consumers worldwide. The variety cultivated depends on the region of planting as the effects of temperature, photoperiod and humidity are the main requirements for strawberry growth. Japan is among the top producers of strawberries with noticeable quality. Malaysia plants strawberries in the highland regions but only for local consumption. Thus, the intended study was done to compare the cultivation and post-harvest practice of strawberries between selected farms in Cameron Highlands, Malaysia and Nagano, Japan. A case study approach was used in this study through questionnaires and informal interviews to obtain the required information on demographics, cultivation practices and technology used by farmers of the selected farms. Based on the obtained information, all four farms in Nagano cultivated strawberries in greenhouses with elevated bed system and irrigation techniques, whereas three of the farms from Cameron Highlands cultivated strawberries by planting in an open area covered with rain shelters. The market value of strawberries from Nagano was also higher compared to Cameron Highlands, despite the minimal differences in farm areas.